2010
DOI: 10.1186/1471-2334-10-163
|View full text |Cite
|
Sign up to set email alerts
|

Tracing the origins and signatures of selection of antifolate resistance in island populations of Plasmodium falciparum

Abstract: BackgroundResistance of the malaria parasite Plasmodium falciparum to sulfadoxine-pyrimethamine (SP) has evolved worldwide. In the archipelago of São Tomé and Principe (STP), West Africa, although SP resistance is highly prevalent the drug is still in use in particular circumstances. To address the evolutionary origins of SP resistance in these islands, we genotyped point mutations at P. falciparum dhfr and dhps genes and analysed microsatellites flanking those genes.MethodsBlood samples were collected in July… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
13
0

Year Published

2013
2013
2017
2017

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 17 publications
(15 citation statements)
references
References 36 publications
2
13
0
Order By: Relevance
“…For example, in Malaria parasites, multiple de novo amplification events of the pfmdr1 gene confer resistance to mefloquine [42], while multiple independent mutations in the genes dhfr and dhps confer resistance to sulfadoxine-pyrimethamine [43]. Several studies have observed soft sweeps during the evolution of drug resistance in HIV [44, 45].…”
Section: Signatures and Examples Of Soft Sweepsmentioning
confidence: 99%
“…For example, in Malaria parasites, multiple de novo amplification events of the pfmdr1 gene confer resistance to mefloquine [42], while multiple independent mutations in the genes dhfr and dhps confer resistance to sulfadoxine-pyrimethamine [43]. Several studies have observed soft sweeps during the evolution of drug resistance in HIV [44, 45].…”
Section: Signatures and Examples Of Soft Sweepsmentioning
confidence: 99%
“…Microsatellites flanking the Pfdhfr (chromosome 4) and Pfdhps (chromosome 8) genes at the following positions were analyzed: for the Pfdhfr gene, loci located 0.3 kb, 4.4 kb, and 5.3 kb upstream of codon 108; and for the Pfdhps gene, loci located 0.8 kb, 4.3 kb, and 7.7 kb downstream of codon 437. The PCR conditions and primers are described in former reports (62,65,67). As a reference, the Southeast Asian P. falciparum K1 laboratory strain was used because its STR profile matches the East African Pfdhps double mutant (GE mutant) haplotype lineage SGE 1 (58).…”
Section: Methodsmentioning
confidence: 99%
“…For haplotype assembly, the resistance-specific polymorphic locus and the corresponding flanking microsatellite loci were considered according to a previous description (67). Isolates for which amplification failed for any of the loci or multiple peaks were generated were excluded from the haplotype grouping.…”
Section: Methodsmentioning
confidence: 99%
“…Additional examples of adaptation from standing variation have been documented in Drosophila (Magwire et al 2011), Peromyscus (Domingues et al 2012), and humans (Peter et al 2012), among others. Adaptations involving simultaneous selection on multiple alleles of independent origin at the same locus have also been documented across a wide array of species (Menozzi et al 2004;Nair et al 2006;Karasov et al 2010;Salgueiro et al 2010;Schmidt et al 2010;Jones et al 2013). Nonetheless, the general importance of soft sweeps for the adaptive process remains somewhat contentious (see, e.g., Jensen 2014; Schrider et al 2015).…”
mentioning
confidence: 99%